Keputusan Pembelian Ulang Melalui Kepuasan Konsumen sebagai Variabel Intervening Ditinjau Dari Kualitas Produk Dan Kualitas Pelayanan Pada Pasar Triwindu Surakarta - Ayu Wardani; Sri Hartono; Eny Kustiyah (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study was to analyze whether the repurchase decision by product quality and service quality in Surakarta Triwindu Market. The population in this study is all consumers in Surakarta Triwindu Market. The sampling technique was accidental sampling, with 100 respondents. Data collection using a Likert scale questionnaire to measure respondent's answers. Path analysis to identify the relationship between product quality and service quality on repurchase decision s through customer satisfaction. The results showed that repurchase decision thought customer satisfaction were not significantly affected by product quality, while service quality on repurchase decisions through customer satisfaction significantly affected the Surakarta Triwindu Market Kerboard : Product quality, Service quality, Customer satisfaction, Repurchase decisions